A Communication Multiplexity Approach to Social Capital: On- and Offline Communication and Self-Esteem. (August 2015) - Rui, Jian Raymond; Covert, Jessica M.; Stefanone, Michael A.; Mukherjee, Tanuka
This study explores the mechanisms by which online social information seeking (i.e., monitoring Facebook friends) relates to social capital. Based on the extant literature, we propose a theoretical framework that includes communication activities across different channels operationalized as offline participation, network structure on social network site operationalized as the number of actual online friends and network diversity, and self-esteem. Results from an online survey ( N = 223) found a moderated mediation model in which participation in offline social activities mediated the relationship between social information seeking and self-reported bonding social capital, and self-esteem moderated this mediation. In addition, participation in offline social activities provided an additional channel to accessing bridging social capital. These results provide a theoretical framework for and suggest an approach of communication multiplexity to future research.